Putusan Mahkamah Konstitusi Nomor 85/PUU-XX/2022: Badan Peradilan Khusus Perkara Perselisihan Hasil Pemilihan Gubernur, Bupati dan Walikota - Yarni, Meri; Indara, Rona; Irwandi, Irwandi; Prasna, Adeb Davega; Juliani, Lauri (Universitas Batanghari Jambi, 2024)
The purpose of this research is to determine and analyze the balance of Constitutional Court Judges in Decision Number 85/PUU-XX/2022 and the legal implications of Decision Number 85/PUU-XX/2022 on special courts for resolving disputes over election results. The research issues include: 1) What are the considerations of Constitutional Court Judges in Decision Number 85/PUU-XX/2022? 2) What are the legal implications of Decision Number 85/PUU-XX/2022 on special courts for resolving disputes over election results? The research method used in this thesis is normative juridical, meaning the research starts from legal issues by analyzing legal problems through legislation, literature, and other reference materials. This thesis employs several approaches, including legal approach, conceptual approach, and case approach. The results of the discussion in this study indicate that: 1) Legal considerations underlying the Constitutional Court Decision include the absence of a special court designated by the President/Government and the DPR to handle disputes over the results of regional head elections, fundamental changes to Article 157 in three amendments to the Regional Head Election Law; the history of the development of authority in resolving disputes over election results in the Constitutional Court; and the elimination of differences in the election regime for both general elections and regional head elections. 2) The implication of constitutional Court Decision number 85/PUU-XX/2022 are, firstly, it removes the role of special judicial bodies in handling disputes over regional elections results” Secondly, there is inconsistency in the Constitutional Court’s decisions, as it previously mandated that settling regional election disputes (PHPUD) is not within the authority of the Constitutional Court. Thirdly, there is a pilin gup of election-related cases in the Constituional Court.